Ionospheric response to variable electric fields in small-scale auroral structures - B. S. Lanchester; M. H. Rees; K. J. F. Sedgemore; J. R. Palmer; H. U. Frey; K. U. Kaila (Annales Geophysicae, 1998)
High time and space resolution optical and radar measurements have revealed the influence of electric fields on E-region electron density profiles in small-scale auroral structures. Large electric fields are present adjacent to auroral filaments produced by monoenergetic electron fluxes. The ionisation profiles measured within and beside the auroral filaments show the effects of plasma convection due to electric fields as well as the consequences of the response time to large and dynamic fluxes of energetic electrons. Without high-resolution optical measurements, the interpretation of the radar data is limited. Key words. Auroral ionosphere · Ionosphere-magnetosphere interactions · EISCAT